An Introduction to Composition Operators in Sobolev Spaces - Bourdaud, Gérard (Eurasian Mathematical Journal, 2023)
We propose a survey of the results on the composition operators in classical Sobolev spaces, obtained between 1975 and 2020. A first version of these notes were the subject of a series of lectures, given in Padova University in January 2018.